High performance multi-purpose nanostructured thin films by inkjet printing: Au micro-electrodes and SERS substrates. Issue 7 (7th March 2023) - Ricci, Simona; Buonomo, Marco; Casalini, Stefano; Bonacchi, Sara; Meneghetti, Moreno; Litti, Lucio
Abstract : Excellent performances in SERS and electronics are obtained for a series of replicates of Au nanoparticle inkjet-printed nanostructured substrates. Abstract : Nanostructured thin metal films are exploited in a wide range of applications, spanning from electrical to optical transducers and sensors. Inkjet printing has become a compliant technique for sustainable, solution-processed, and cost-effective thin films fabrication. Inspired by the principles of green chemistry, here we show two novel formulations of Au nanoparticle-based inks for manufacturing nanostructured and conductive thin films by using inkjet printing. This approach showed the feasibility to minimize the use of two limiting factors, namely stabilizers and sintering. The extensive morphological and structural characterization provides pieces of evidence about how the nanotextures lead to high electrical and optical performances. Our conductive films (sheet resistance equal to 10.8 ± 4.1 Ω per square) are a few hundred nanometres thick and feature remarkable optical properties in terms of SERS activity with enhancement factors as high as 10 7 averaged on the mm 2 scale. Our proof-of-concept succeeded in simultaneously combining electrochemistry and SERS by means of real-time tracking of the specific signal of mercaptobenzoic acid cast on our nanostructured electrode.